Proteção social e medidas socioeducativas em meio aberto: garantia de direitos ou punição? - Oliveira, Maria Cristina de (2022)
This thesis aimed to analyze the social protection of the social assistance policy in the monitoring of adolescents in open social-educational measures in the ABCDMRR region of São Paulo. The research was based on the critical theory of Marxist inspiration, incorporating principles of historical materialism in the investigative process. As theoretical and conceptual references, we resorted to authors who discuss social policy, social assistance policy, human rights of children and adolescents, and the racial issue. Along with the bibliographical reference and the analysis of legalnormative documents, the focal group technique was used, in four meetings, with the participation of 17 professionals from the areas of Psychology, Social Work, Law, and Pedagogy who work directly with adolescents, young people, and their families. From the invitation to all the executive teams of the open social and educational measures (seven municipalities), professionals from four units accepted to participate (Creas Diadema, Creas Rio Grande da Serra, Creas Santo André, and Fundação Criança de São Bernardo do Campo). The meetings were based on seven guiding questions: 1) What is the understanding of social protection in the social welfare policy? 2) What is the meaning of the fulfillment of socio-educational measures in an open environment for professionals of direct attention in the monitoring of adolescents? 3) Does social protection in social assistance policy guarantee rights or is it a form of punishment in the fulfillment of open social and educational measures? 4) What is the group's understanding of the racial issue and the MSEs? 5) Does the attention provided by the MSE execution team reach the social protection objectives? What is the evaluation of the area? 6) What is the evaluation of the direct execution carried out by the public power and the indirect execution, carried out by non-state entities? 7) In the monitoring of socio-educational measures in an open environment, is there inter-sectionality and inter-institutionality? It was possible to understand that, in spite of the achievements of the Child and Adolescent Statute, we still need to advance in the actions related to the socio-educative measures in an open environment, to accomplish the implementation of the System of Rights Guarantee, recognizing as subjects of rights adolescents/youth to whom it is attributed the practice of infractional act. It is, therefore, a matter of breaking with the marks of the punitive paradigm, wherever they manifest themselves, ensuring effective integral protection